Nanocompósito à base de hidroxietilamido para o carreamento magnético de oncocalixona-A e aumento de penetração dérmica por magnetoforese negativa - Sousa, Alexandre Carreira da Cruz (2023)
Magnetic nanocarriers have been adopted as an innovative therapeutic strategy, enabling drug targeting through magnetophoresis on different kinds of therapies, which can improve drug bioavailability. Starch-based magnetic nanocapsules were synthesized for the targeted delivery of a hydrophilic bioactive called oncocalyxone A (onco-A) through the application of an external magnetic field. The synthesis by inverse miniemulsion technique allowed the co-encapsulation of superparamagnetic iron oxide nanoparticles (SPIONs) and onco-A into the same nanostructure, generating a magnetic behavior and anticancer activity, respectively, for the synthesized nanocomposite. The synthesized nanocapsules exhibited a core-shell morphology and an average diameter of 143 nm. This nanocomposite showed potential anticancer activity (IC50 – 72h) against four human tumor cell lines: glioblastoma SNB-19 (1.010 gmL-1), colon carcinoma HCT-116 (2.675 gmL-1), prostate PC3 (4.868 gmL-1) and leukemia HL-60 (2.166 gmL-1). In vivo acute toxicity (96h) and locomotor activity were evaluated in a zebrafish (Danio rerio) model. Thus, the synthesized nanocomposite exhibited in vivo biocompatibility, prolonged drug release profile, in vitro antitumor activity, and also responded to an applied magnetic field, generating a promising compound for magnetic vectorization of drugs. Additionally, for the first time, it was evaluated the effect of a magnetic field on the transdermal drug penetration (targeted, or not, to the hair follicle by negative magnetophoresis), demonstrating an average of up to 340% higher skin penetration of adapalene or fluorescein, under magnetophoresis, when compared to the passive penetration. Furthermore, although the mechanism of penetration enhancement has not yet been elucidated, it was evidenced that this penetration increase occurs not only through the follicular pathway, but also through transcellular and/or intercellular routes through the stratum corneum.